CONSUMER PURCHASE DECISIONS IN TIKTOK LIVE: ANALYZING THE ROLE OF INFLUENCER CREDIBILITY, IMMERSION, AND ENGAGEMENT - Ana Rimbasari; Agniya Thahira (CAPITAL: Jurnal Ekonomi dan Manajemen, 2024)
This study examines the impact of influencer credibility, immersion, and involvement on purchase decisions through TikTok Live. Employing a quantitative method, the research collected data from 250 active TikTok users participating in Live sessions. The findings indicate that influencer credibility, immersion, and involvement significantly influence purchase decisions, with influencer credibility being the most dominant factor. The study recommends strategies to enhance engagement and immersion during Live sessions to strengthen the impact of influencer credibility. These insights provide digital marketers with guidance on optimizing influencer marketing strategies on TikTok.